Implementing cycling infrastructure in a politicized space: Lessons from Toronto, Canada. (June 2020) - Wilson, Adam; Mitra, Raktim
Abstract: Cycling infrastructure such as cycle tracks and painted bicycle lanes is critical in improving safety of existing cyclists and in increasing the overall mode share of bicycling in communities. However, the implementation of such infrastructure has been fraught with political contentiousness across North America. In this paper, we discuss how theories of automobility and the politics around it may help explain current active transportation planning practice. We then report findings from ten key informant interviews with municipal planners and engineers in the Greater Toronto and Hamilton Area, Canada, in order to identify how they implement cycling infrastructure in the face of political opposition. We find that there are four principal strategies used to secure the political support and ensure the construction of cycling infrastructure across the region: 1) piggybacking on public works projects, 2) using external grants and funding, 3) pre-emptively re-routing cycling infrastructure, and 4) finding support from a political champion. Based on these findings, we conclude that the politicization of cycling infrastructure is a result of the dominance of automobility in Western transportation culture. In other words, it is not the physical presence of the cycling infrastructure, nor its social and political representations, but rather automobile that is political, and a battle for (road)space against it remains and may continue to remain a major policy and professional challenge. Highlights: Cycling infrastructure is often considered as an affront to the automobile and automobility. The politicization of cycling infrastructure likely occurs as a result of automobility. Bicycle only becomes a politically charged topic when pushed in opposition to automobiles. Four key strategies were identified as common practices to navigate the political landscape in order to build new cycling infrastructure.